Corruption as a Key Transmission Channel Linking Governance and Investor Protection in ASEAN - Muhammad Firmansyah; Yuli, Sri Budi Cantika; Fitriasari, Fika; Arifin, Zainal; Flejterski, Stanislaw (ETIKONOMI, 2026)
Research Originality: The Originality lies in integrating governance quality and macroeconomic variables within a unified framework while explicitly modeling corruption as a mediating variable, a focus that remains underexplored in prior studies. Research Objectives: This study examines the role of corruption as a transmission mechanism linking governance and macroeconomic factors to investor protection in ASEAN countries. Research Method: Using panel data from six ASEAN countries over the period 2010–2023, this study applies panel-data-based path analysis with bootstrapping to estimate both direct and indirect effects. Robustness checks are conducted using fixed-effects, random-effects, and System GMM estimators to ensure the consistency of the results. Empirical Results: The findings show that governance significantly enhances investor protection, while portfolio investment and interest rates exhibit varying effects depending on institutional conditions. Importantly, corruption is found to play a significant mediating role, indicating that improvements in governance and macroeconomic performance do not automatically strengthen investor protection without effective corruption control. Implications: This study suggests that policymakers should integrate governance reforms with anti-corruption strategies to improve investor protection. Strengthening institutional quality, transparency, and regulatory enforcement is essential to create a more secure and sustainable investment environment in ASEAN economies.  JEL Classification: D73, G38, F21, E44